2011
DOI: 10.1007/s10567-011-0105-4
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Anxiety Disorders: Considering the Contributions of Attachment and Emotion Regulation

Abstract: Anxiety disorders are among the most common psychiatric disorders in childhood. Nonetheless, theoretical knowledge of the development and maintenance of childhood anxiety disorders is still in its infancy. Recently, research has begun to investigate the influence of emotion regulation on anxiety disorders. Although a relation between anxiety disorders and emotion regulation difficulties has been demonstrated, little attention has been given to the question of why anxious individuals have difficulties regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 86 publications
4
56
1
3
Order By: Relevance
“…In other words, assimilation may build a bridge between a negative internal working model of the self and problem behaviors. This is in line with research indicating that insecure attachment may put children on a path toward developing problem behaviors or psychiatric symptoms (Ciocca et al 2017;Esbjorn et al 2012;Guttmann-Steinmetz and Crowell 2006).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In other words, assimilation may build a bridge between a negative internal working model of the self and problem behaviors. This is in line with research indicating that insecure attachment may put children on a path toward developing problem behaviors or psychiatric symptoms (Ciocca et al 2017;Esbjorn et al 2012;Guttmann-Steinmetz and Crowell 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Possible mechanisms discussed included parental attunement and mentalization. (Porcerelli et al 2016) A large body of research has shown that an individual's attachment style influences a range of psychological and social factors (Ravitz et al 2010), including externalizing behavior problems (Guttmann-Steinmetz and Crowell 2006), internalizing psychiatric symptoms (Esbjorn et al 2012), and emotion regulation (Esbjorn et al 2012;Gillath et al 2005;Guttmann-Steinmetz and Crowell 2006;Moutsiana et al 2014;Roque et al 2013). Insecure maternal attachment was found to be associated with depression in ADHD children.…”
Section: Introductionmentioning
confidence: 99%
“…Emotion dysregulation, conceptualized as comprising difficulties in any or all of these abilities (Gratz and Roemer 2004), has been linked to various psychological problems, including anxiety (e.g., Turk et al 2005). Insecure working models of attachment generally showed positive associations with emotion dysregulation and with symptoms of both anxiety and depression (e.g., Bender et al 2015;Esbjørn et al 2012;*Kullik and Petermann 2013;Marganska et al 2013), suggesting that attachment insecurity may promote maladaptive emotion regulation strategies and thus increasing the risk for these internalizing symptoms in adolescence (e.g., Allen et al 1996).…”
Section: Internalizing Symptoms and Peer Attachmentmentioning
confidence: 99%
“…Este aspecto se considera relevante toda vez que las dificultades en la regulación emocional (en adelante DRE) se encuentran presentes en una serie de problemas de salud mental, como la violencia (e.g., Lafontaine & Lussier, 2005), el trastorno de personalidad limítrofe (Glenn & Klonsky, 2009) y los trastornos de ansiedad (e.g., Esbjørn, Bender, Reinholdt-Dunne, Munck & Ollendick, 2012;Mennin, Holaway, Fresco, Moore & Heimberg, 2007), por mencionar algunos.…”
unclassified